Biological activities of four varieties of ficus deltoidea (jack) and correlation to their flavonoid content / Syazwani Dzolin - Dzolin, Syazwani (2014)
In this study, the aqueous leaves and figs extracts of four varieties of Ficus deltoidea (Fd) namely Fdvk (kunstleri), Fdva (angustifolia), Fdvd (deltoidea) and Fdvi {intermedia) were estimated for their total phenolic and total flavonoid contents, and evaluated for their in vitro antioxidant, a-glucosidase inhibitory and neuroprotective effects. Their flavonoid constituents and their correlation with their biological activities were also investigated. The TPC and TFC assays estimated that high content of total phenolics (89.10-99.60 mg GAE/g extract) for extracts of Fdvd and Fdvi but total flavonoids content was significantly higher in Fdvd. In the FTC antioxidant assay, the leaves and figs extracts of both Fdvd and Fdvi showed high percent of inhibition of more than 95% in the FTC assay and 73-79% in the TBA assay. The figs extracts of these two varieties (Fdvd and Fdvi) also exhibited strong radical scavenging activity in the DPPH assay, with ICsoof 7.8 |ig/ml. Interestingly, only the leaves extract of both varieties displayed higher inhibition towards a-glucosidase (Fdvd > Fdvi > Fdvk > Fdva) compared to the other two varieties and compared to the figs extract indicating the presence of more antidiabetic constituents in the leaves. In the neurotoxicity assay, all samples exhibited no signs of toxicity (> 50% cell viability) against SH-SY5Y neuroblastoma cell and displayed potential neuroprotective effects against H202-indueed toxicity cells. Fdvd and Fdvi (leaves and figs) showed good neuroprotective potential indicated by high percent of cell viability as determined by the MTS assay. Following chromatography of extracts on a reversed phase Cis column, LCMS Q-TOF identified the marker flavonoids of the plants from their m/z values as well as by comparison with internal standards. Employing the HCA technique, a dendrogram representing four clusters of flavonoids distribution in the eight samples (based on its distribution values) comprising ep/catechin, quercetin-3- rutinoside, quercetin 5,4'-di-0-beta-Z)-glucopyranoside, myricetin and naringenin were successfully generated. A good correlation was observed between the flavonoid distributions in each plant variety to its biological activities. In conclusion, this study found that the strong activity of Fdvd and Fdvi could be correlated to the presence of the antioxidant epz'catechin relatively high amounts in both varieties.